Crime time: How ambient light affects crime - Patricio Domínguez; Kenzo Asahi (Inter-American Development Bank (IDB), 2019)
This paper studies the effect of ambient light on crime, taking advantage of the daylight saving time (DST) policy, which imposes exogenous variations in daylight exposure at specific hours of the day. The paper uses a rich administrative database managed by Chile's national police, a centralized agency that collects detailed information regarding each crime incident. A 20% decrease (increase) in crimes is found when the DST transition increases (decreases) the amount of sunlight by one hour during the 7-9 p.m. period. Importantly, no significant response is detected induced by DST associated with a plausible demand-side response such as the population's commuting time pattern, and no substantial short-term displacement is found. Most of the changes in property crime due to the DST policy are driven by robbery in residential areas.
Keywords: K42; R41; D01; 330; Economics of crime; Daylight Saving Time; Rational choice